Pengaruh Strategi Promosi Voucher Berbasis Lokasi di TikTok terhadap Minat Beli Konsumen - Azril Akbar Agustiyanti; Chaerudin Chaerudin (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyze the effect of location-based voucher promotion strategies on TikTok toward consumer purchase intention, in line with the growing adoption of digital marketing technologies that utilize location-personalized features. The research problem concerns the lack of empirical evidence regarding the effectiveness of location-based promotions in influencing purchase intention, since most prior studies focused on general discounts, price promotions, or influencer marketing. A quantitative method was employed by distributing Likert-scale questionnaires to 100 active TikTok users exposed to location-based promotional vouchers. The data were analyzed using simple linear regression to examine the effect of promotional strategy variables on purchase intention. The findings indicate that loca-tion-based promotion strategies have a positive and significant effect on purchase intention, as reflected by a regression coefficient of 0,701 and a significance value of 0.000. The R² value of 0.417 shows that 41.7% of the variation in purchase intention is explained by the applied promotional strategy. These results indicate that relevant, contextual, and location-personalized promotions effectively increase consumers’ purchasing tendencies. The study concludes that the use of location-based vouchers on TikTok is an efficient and impactful promotional strategy, providing important implications for busi-nesses in designing more targeted digital marketing activities.